PROGRAM BUDAYA MADRASAH DALAM MENINGKATKAN DAYA SAING MADRASAH - Sevia Umi Wardini; Nihayatul Laili Yuhana; Fathur Rochim (STAI KH. Muhammad Ali Shodiq, 2023)
Madrasah culture is indeed a barometer of Madrasah activities which is a measure of whether the Madrasah has a culture that produces good results for Madrasas or vice versa a bad culture for Madrasahs, therefore prioritize Madrasah Culture in increasing competitiveness institutions so that these institutions have good icons and habits in daily life in madrasas so as to increase the competitiveness of madrasah. the purpose of this research is to find and analyze the Madrasah cultural program in increasing competitiveness. This study uses a qualitative approach with a multi-site study design. Data collection in this study used in-depth interviews, observation, and documentation techniques in which the data sources were people , documents ( papers ) and places ( place ). The results of this study fully strengthen the theory of the Culture of a School conveyed by strengthening the theories of Beare, Caldwell, Spinks and Milikan that the main principle in Madrasah Culture is the Madrasah Culture Program which contains goals and objectives ( Aims and objectives ), Curriculum ( Curriculum ), language ( Language ), Thought ( Metaphor ) and Organizing ( Organizational).